2019
DOI: 10.1111/opn.12239
|View full text |Cite
|
Sign up to set email alerts
|

How do “robopets” impact the health and well‐being of residents in care homes? A systematic review of qualitative and quantitative evidence

Abstract: Background Robopets are small animal‐like robots which have the appearance and behavioural characteristics of pets. Objective To bring together the evidence of the experiences of staff, residents and family members of interacting with robopets and the effects of robopets on the health and well‐being of older people living in care homes. Design Systematic review of qualitative and quantitative research. Data sources We searched 13 electronic databases from inception to July 2018 and undertook forward and backwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 63 publications
(335 reference statements)
6
110
2
1
Order By: Relevance
“…Longitudinal studies can provide the opportunity to investigate whether fear of using a new and unfamiliar technology, or losing interest in a new technology (diminishing novelty effect), are related to negative attitudes. Abbott et al 8 in their review of the use of social robotic pets (animal-like social robots) found similar mixed feelings from the different stakeholders. The fact that people have very strong feelings on the opposite sides of the spectrum, either very positive or very negative, is significant to implementation and requires a careful investigation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Longitudinal studies can provide the opportunity to investigate whether fear of using a new and unfamiliar technology, or losing interest in a new technology (diminishing novelty effect), are related to negative attitudes. Abbott et al 8 in their review of the use of social robotic pets (animal-like social robots) found similar mixed feelings from the different stakeholders. The fact that people have very strong feelings on the opposite sides of the spectrum, either very positive or very negative, is significant to implementation and requires a careful investigation.…”
Section: Discussionmentioning
confidence: 95%
“…In a systematic review of the literature about the use of different available technologies directed to assist older adults, robotic devices and robots were viewed as an encouraging technology that can assist and prolong older adults’ independent living 5. Corroborating this finding, a few additional reviews of the literature have indicated that: (i) SAHRs could have multiple roles in the care of older adults such as in affective therapy and cognitive training6 and (ii) they could be beneficial in reducing anxiety, agitation, loneliness and improving quality of life, engagement and interaction (especially when used as a therapeutic tool when caring for patients with dementia) 7–9. In addition, reviews related to the acceptance of robots have found it being influenced by numerous factors, such as the perceived need for the technology, the user’s previous experiences with it, age, level of education, expectations about what the technology can do, attitudes and cultural background;10 in fact, robots that were programmed to use verbal and non-verbal communication familiar to the user and to their cultural background were more easily accepted by users 11.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, systolic and diastolic blood pressure decreased signi icantly from baseline in residents following an interaction with a seal companion robot, Paro [33]. Similarly, reported loneliness and depression decreased due to discussing and talking to the robot [34]. Robopets in general, including Paro, have a positive impact on the general physical health, well-being and quality of life among older people living in care homes, and also signi icantly reduce agitation (by 68%), as shown in a systematic review of 19 studies [35].…”
Section: Assisted Technology In Geriatric Care and Rehabilitation: Romentioning
confidence: 91%
“…However, as 40 % of the Norwegian population hold animals as pets [35], and this number falls below 10 % for older adults [36], this area might be explored; especially as pets have positive effects on well-being [37]. Experiments with digital pets have produced varied results, but with a positive tendency [7,38,39].…”
Section: Technologies and Capabilitiesmentioning
confidence: 99%